Collaboration of Counseling Teachers and Parents in Distance Learning During The Covid-19 Pandemic - Rio, Rio Hermawan (International Journal of Applied Guidance and Counseling, 2021)
Abstrak:Â This research is a type of descriptive analytic study, which explains and analyzes how the collaboration of counseling teachers and parents in distance learning during the Covid-19 pandemic. During distance learning the bk teacher should consider increasing communication interaction with parents as well as collaborating with parents and trying to develop positive perceptions about students in terms of student success during distance learning. Collaboration is an activity where there is cooperation between various parties in realizing educational goals, both parties from within and from outside educational institutions. Collaboration in guidance and counseling is a collaborative activity between counseling teachers and a number of related parties in order to achieve the objectives of the guidance and counseling service program, therefore there is a need for a good collaborative strategy between counselors and parents, especially in terms of developing student study success. The involvement of parents in question can be in the form of inviting parents as members of the school committee, providing opportunities for parents to become tutors in an instructional program, involvement of parents in funding a broader school program and also strengthening the understanding and skills of parents regarding child and adult development.